FAKTOR-FAKTOR YANG MEMPENGARUHI POLA TANAM DAN PENDAPATAN PETANI PADA BERBAGAI KETERSEDIAAN AIR DI DAERAH IRIGASI KARANGLO - Rizkia Nailir Rahma; M. Rondhi; Anik Suwandari (UNEJ e-Proceeding, 2018)
One of the technical irrigation networks in Jember Regency is Karanglo irrigation region with an area of 2334 Ha. There were two parts of the irrigation flow, the upstream and downstream. The upstream section is located in Tanggul Wetan Village and the downstream section is located in Bangsalsari Village. this research is aimed to (1) Knowing farming pattern applied by farmers in Karanglo irrigation area of Jember Regency, (2) to knowing factors that influence farmers in Karanglo irrigation area in choosing cropping pattern that will be applied for a year and (3) to knowing Difference of Farmers Incomes with various patterns of planting at Karanglo irrigation region. The research used descriptive and analytic method. The research data that used were primary and secondary data. The results of the analysis show that: (1) there were 3 planting pattern at Gambirono village, which is rice-rice-rice, paddy-rice-corn, and paddy-rice-soy (2) Factors that had real effect on farmer decision making in applying the cropping pattern for a year were profit and labor, and, (3) There were differences of farmer's income. The greatest income is obtained by the farmer applying cropping pattern 1 (paddy-rice-paddy).